HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP DENGAN TINDAKAN PENCEGAHAN INFEKSI SALURAN PERNAPASAN AKUT PADA LANSIA DI KECAMATAN WANEA KOTA MANADO - Sambeka, Meira; Kairupan, Carla F; Nurmansyah, Muhamad (Universitas Sam Ratulangi, 2024)
Background: Acute respiratory infections are the leading cause of infectious diseases and the most important cause of death in the world, most deaths occur in the elderly so that this disease requires preventive measures to avoid disease. Objective: of knowing the relationship between knowledge level and attitude with preventive measures for acute respiratory infections in the elderly in Wanea District, Manado City. Method: uses a type of quantitative research with a correlation analytic research method using a cross sectional study approach, with a sample size of 100 respondents. Results: of the study using the Kolmogorov-Smirnov test with the result of p=0.992 for the relationship between the level of knowledge and the prevention of acute respiratory infections and using the fisher test with the result of p=0.061 for the relationship between attitudes and the prevention of acute respiratory infections. Conclusion: there is no significant relationship between the level of knowledge and the prevention of acute respiratory infections and there is no significant relationship between attitudes and the prevention of acute respiratory infections. Keywords: Acute Respiratory Tract Infection; Attitude; Elderly; Knowledge Level; Preventive Measures for Acute Respiratory Tract Infection.